المسؤولية الاجتماعية للمصارف الإسلامية في ضوء مقاصد الشريعة : مصرف الراجحي نموذجا - Fakhriyah Ibrahim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Islamic banks are embodied as financial institutions which seek to achieve social role in banking activities in accordance with the percepts of Al-Shariʼah Islamiah One of the Islamic banks in The Kingdom of Saudi Arabia is studied to clarify the concepts of social responsibility, social development objectives and activities. Furthermore, this research examines the performance measurement of social responsibility based on Islamic banking standards, financial and forensic. In other words, this paper attempts to understand the extent of their application and their interaction among banks along with their banking products. Particularly, the study analyses discourses to ideality direct and indirect social activities where the practical application of the profitability of standard for financial measurement and measurement criteria for legitimate legal control are highlighted, The research used inductive and deductive approaches by applying analytical and mathematical equations and performance measurement indicators, demonstrating the processes in tables, figures and graphs and time series, This paper concludes that the determination of social responsibility practices of Islamic banks can be done through application of legitimate criterion of the Shari'ah and financial standard profitability index, This has been proven as available in the Al Rajhi Bank's activities and banking services in terms of their continuous and significant development covering the period of 2008 until 2013 moreover, this study asserts that we can consider the index as an essential paramedic in many cases, including insolvency in religious cases as a substitute for interest in conventional banks. this is achieved by Al-Rajhi Bank in terms of the purposes of private financial dispositions from the Shari'ah perspective and in terms of the vision of Maqasid, necessary and needed in promoting in banking products and services